Born to rock - Patterson, James, 1947-; Tebbetts, Christopher (Patterson, James, 1947- Middle school novels., 2019)
Georgia Khatchadorian has a lot of her plate: she's got a super secret crush on Sam Marks, a Rube Goldberg machine challenge to win, and she has to deal with mean girl Missy Trillin and her Princess Patrol. But when Georgia's favorite band, Lulu and the Handbags, announces a competition where the winning band gets to jam with Lulu herself, Georgia pulls out all the stops to make sure that her band, We Stink, wins, even if it means asking her older brother Rafe for help.